Improving The Quality of Education: Implementation of School-Based Quality Improvement Management - Badrud Tamam; Cucun Sunaengsih; Diana Fatimah Ratnasari; Yuliana Yuliana; Aminudin Aminudin (MASI Mandiri Edukasi, 2025)
This study explores the implementation of School-Based Quality Improvement Management (MPMBS) in elementary schools across Bandung Regency, Indonesia. MPMBS represents an autonomy-driven management model emphasising participatory decision-making and collective responsibility to enhance educational quality. Using a descriptive qualitative method, data were collected through online questionnaires and semi-structured interviews involving school principals and teachers. The analysis focused on leadership roles, participatory planning, and factors influencing implementation. Findings indicate that school principals demonstrate visionary leadership by fostering collaboration among teachers, parents, and community stakeholders. MPMBS has been effectively implemented in most schools, although challenges remain—particularly limited financial resources, inadequate infrastructure, and issues with teacher motivation. The study concludes that effective implementation of MPMBS depends on strong leadership, resource optimisation, and effective stakeholder engagement. It recommends targeted professional development, resource allocation, and policy reinforcement to strengthen quality improvement practices in primary education. These insights offer practical guidance for educational policymakers and school leaders seeking sustainable management strategies in decentralised educational settings.